Evaluating anticipatory control strategies for their capability to cope with step-down perturbations in computer simulations of human walking - Lucas Schreff; Daniel F. B. Haeufle; Johanna Vielemeyer; Roy Müller (Scientific Reports, 2022)
Abstract Previous simulation studies investigated the role of reflexes and central pattern generators to explain the kinematic and dynamic adaptations in reaction to step-down perturbations. However, experiments also show preparatory adaptations in humans based on visual anticipation of a perturbation. In this study, we propose a high-level anticipatory strategy augmenting a low-level muscle-reflex control. This strategy directly changes the gain of the reflex control exclusively during the last contact prior to a drop in ground level. Our simulations show that especially the anticipatory reduction of soleus activity and the increase of hamstrings activity result in higher robustness. The best results were obtained when the change in stimulation of the soleus muscle occurred 300 ms after the heel strike of the contralateral leg. This enabled the model to descend perturbation heights up to − 0.21 m and the resulting kinematic and dynamic adaptations are similar to the experimental observations. This proves that the anticipatory strategy observed in experiments has the purpose of increasing robustness. Furthermore, this strategy outperforms other reactive strategies, e.g., pure feedback control or combined feedback and feed-forward control, with maximum perturbation heights of − 0.03 and − 0.07 m, respectively.